Bullying Behaviour Intensity Reviewed from the Perception of School Climate on High School Students - Julianto Julianto; Sri Hartini; Winida Marpaung (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study examines the intensity of bullying behaviour based on the perception of school climate among high school students. The sample of this study is 243 students from grades 10 and 11 of one of the private schools in Kecamatan Medan Sunggal, Medan who were randomly selected by using disproportionate stratified random sampling. Data were collected using an Indonesian adaptation and translation of the MDS3 Climate Survey scale to measure school climate perception and the Bullying and Cyberbullying Scales for Adolescents (BCS-A) perpetration dimension to measure the intensity of bullying behaviour. The collected data were then analysed using correlational statistical techniques and Spearman's rho correlation test. The data analysis showed a negative correlation with the value of -0.508 (p < 0.05), which indicates a moderate correlation between the variable of school climate perception and bullying behaviour intensity, where the negative correlation means that the better the perception of school climate, the lower the bullying behaviour intensity, and vice versa, where the lower the perception of school climate, the higher the bullying behaviour intensity. Penelitian ini meneliti tentang intensitas perilaku bullying ditinjau dari persepsi iklim sekolah pada peserta didik tingkat Sekolah Menengah Atas (SMA). Sampel pada penelitian ini adalah 243 peserta didik tingkat X dan XI salah satu SMA Swasta yang terletak di Kecamatan Medan Sunggal, Kota Medan. Sampel dipilih secara acak menggunakan teknik disproportionate stratified random sampling. Data dikumpulkan menggunakan adaptasi dan terjemahan Bahasa Indonesia dari skala MDS3 Climate Surey untuk mengukur persepsi iklim sekolah dan skala Bullying and Cyberbullying Scales for Adolescents (BCS-A) dimensi perpetration untuk mengukur intensitas perilaku bullying. Data dianalisis menggunakan teknik statistik korelasional Spearman’s rho. Hasil analisis data menunjukkan bahwa terdapat korelasi negatif sebesar -0,508 (p < 0,05) yang dapat disimpulkan bahwa terdapat korelasi sedang variabel persepsi iklim sekolah dengan intensitas perilaku bullying, dengan korelasi negatif yang berarti semakin baik persepsi iklim sekolah maka semakin rendah intensitas perilaku bullying dan sebaliknya, rendah persepsi iklim sekolah maka semakin tinggi intensitas perilaku bullying.